Harmonizing Talent and Culture: Unveiling the Success Story of PT Linde Indonesia's Employee Engagement Revolution through Strategic Employer Branding Harmonizing Talent and Culture: Unveiling the Success Story of PT Linde Indonesia's Employee Engagement Revolution through Strategic Employer Branding - Chrisselda Putri Hendrita; Agung Surya Dwianto (STIE AMKOP, 2023)
This qualitative research investigates the dynamic interplay between employer branding and employee engagement within the context of PT Linde Indonesia. The study aims to uncover the nuanced factors that contribute to, or hinder, employee engagement as influenced by the organization's employer branding strategies. Employing a case study approach, the research delves into the experiences and perceptions of employees to provide a comprehensive understanding of the linkages between employer branding initiatives and the level of engagement among the workforce. The research methodology involves in-depth interviews and document analysis to triangulate data and ensure robust findings. Preliminary analysis reveals a multifaceted relationship between employer branding elements, such as organizational culture, communication strategies, and perceived value propositions, and the employees' emotional and cognitive engagement. Notably, the study identifies key themes emerging from participant narratives, shedding light on the complex ways in which employer branding influences the overall employee experience. The findings of this research contribute to both academic discourse and practical implications for organizational management. By unraveling the intricate connections between employer branding and employee engagement, organizations, including PT Linde Indonesia, can gain insights into refining their branding strategies to foster a more engaged and motivated workforce. Additionally, the study underscores the importance of aligning employer branding efforts with the unique organizational culture and values to maximize their impact on employee engagement. Keywords: Employee Engagement, Employer Branding